Vereinbarkeit von Familie und Beruf für Ärztinnen in Deutschland am Beispiel der Urologie - Wiemer, Laura Elisa; Knipper, Sophie; Herlemann, Annika; Welte, Maria-Noemi; Siech, Carolin; Greiser, Eva-Maria; Müller, Karina; Bellut, Laura; Schönburg, Sandra; Walach, Margarete; Pompe, Raisa; Weinberger, Sarah (Die Urologie, 2024)
Background The shortage of skilled labor in medicine is one of the most pressing challenges in healthcare. The increasing number of women in medicine, particularly in the field of urology, raises questions about the compatibility of family and career, especially concerning the work environment and working time models. Objective The aim of this study is to capture the impact of motherhood on the professional lives of female physicians and scientists in the field of urology in Germany. Specific challenges in this surgical specialty and the compatibility of family and career will be highlighted. Methods The working group “Female Physicians and Scientists in Urology” of the German Society of Urology (DGU) surveyed its 1343 female members regarding demographic data, professional status, and aspects of work-life balance. Results Among 487 female urologists in Germany, 53.4% had children. Mothers tended to be older, less frequently in training, less often in inpatient settings, and less frequently engaged in surgical activities. Notably, the proportion of full-time working mothers (36.2%) was significantly lower compared to female urologists without children (92.4%). Among female urologists with children, 32.3% reported having changed their workplace because of their children, while 10.7% indicated that their responsibilities had changed at least once after pregnancy. Additionally, 76.9% of mothers had reduced their weekly working hours due to family commitments. Multivariate analysis showed an influence of motherhood on professional status and parttime work. Conclusion The fact that starting a family for women in urology in Germany is associated with a reduction in working hours and the end of clinical careers suggests a need for optimizing the compatibility of family and career in Germany. The increasing feminization of the medical profession exacerbates the existing shortage of skilled workers due to the exit of mothers from professional life. To meet the needs of working parents, particularly mothers, urgent adjustments in the work environment are necessary. Promoting flexible working time models and creating supportive conditions are crucial to preventing the loss of skilled professionals and maintaining job satisfaction in this field.